Inverted-T shape incision as a successful method of visualization of left atrial myxoma which is located atypically - Zwoliński, Radosław; Ostrowski, Stanisław; Bartczak, Karol; Piestrzeniewicz, Katarzyna; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
71 years old asymptomatic female with left atrial myxoma with broad base, located in the superior part of interatrial septum beneath superior caval vane, was admitted to the hospital for surgery. Due to difficult access and small size of left atrium we did inverted T shape incision to visualize the tumor better. This approach enabled total excision of the tumor with preservation of oncological resection margin and suture of the big loss of interatrial septum with pericardial patch without any problem.